Mandibular bone healing after advancement or setback surgery using sagittal split ramus osteotomy. Issue 9 (September 2018) - Ueki, Koichiro; Moroi, Akinori; Tsutsui, Takamitsu; Hotta, Asami; Hiraide, Ryota; Takayama, Akihiro; Tsunoda, Tatsuya; Saito, Yuki; Sato, Momoko; Baba, Nana; Yoshizawa, Kunio
Abstract: Purpose: The purpose of this study was to compare mandibular bone healing after advancement or setback surgery using sagittal split ramus osteotomy (SSRO). Subjects: and Methods. The subjects were 50 patients (100 sides) who underwent bi-maxillary surgery, and were divided into 2 groups (25 class II advancement cases and 25 class III setback cases). They were selected randomly from the patients who underwent surgery between 2012 and 2017. Ramus square, ramus length and ramus width were measured in the horizontal plane image of computed tomography (CT), before and immediately after the operation, and at 1 year after the operation. Results: Ramus square in the class III cases significantly increased in 1 year after the operation (P < 0.0001), meanwhile there was no change after 1 year in the class II cases. Before the operation, there were no significant differences in the all measurements between classes II and III. However, for ramus width, class III was significantly larger than class II immediately after (P = 0.0014) and at 1 year after the operation (P = 0.0003). Conclusion: This study suggested that post-operative change in ramus morphology was different between class II advancement surgery and class III setback surgery.